Alcohol Intake is Associated with Increased Risk of Squamous Cell Carcinoma of the Skin: Three US Prospective Cohort Studies. (18th May 2016) - Siiskonen, Satu; Han, Jiali; Li, Tricia; Cho, Eunyoung; Nijsten, Tamar; Qureshi, Abrar
ABSTRACT: The association between alcohol intake and cutaneous squamous cell carcinoma (cSCC) is unclear. We studied the association between alcohol intake and incident invasive cSCC in three cohorts of women and men with repeated assessments of alcohol intake in the US. Information on alcohol intake was collected repeatedly during follow-up. Cumulative average of alcohol intakes was used. Multivariable Cox proportional hazards models with time-dependent exposure were used to estimate relative risks (RRs) and 95% confidence intervals, followed by a meta-analysis. During a follow-up of 4, 234, 416 person-years, 2, 938 cSCC were identified. Alcohol intake was associated with an increased risk of cSCC with a dose-response relationship. Each additional drink (12.8 gram of alcohol) per day was associated with a 22% increased risk of cSCC (RR 1.22, 95% confidence interval: 1.13–1.31). White wine consumption of ≥5 times/wk was associated with an increased risk of cSCC (RR 1.31, 95% confidence interval: 1.09–1.59). We found no increased risk of cSCC with other alcoholic beverages. The population-attributable risk associated with alcohol intake of ≥20 grams/d was 3% of cSCCs. In conclusion, alcohol intake was associated with an elevated risk of cSCC. Among alcoholic beverages, white wine was associated with cSCC.